Importer price effects of tariffs in the context of preferential trade agreements: The case of poultry in South Africa - Jing Woei Chien; Lawrence Edwards; Ayanda Hlatshwayo (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2024)
Using highly disaggregated customs-transaction-level data, we study the importer price effects of tariffs in the context of preferential trade agreements for South African imports of frozen bone-in chicken. We focus first on the firm-level impact of tariffs on import prices. Findings suggest no pass-through effect from changes in tariffs but our quantity analysis contradicts this, indicating adjustments consistent with higher landed prices. We reconcile this by considering the impact of the extensive margin with the inclusion of zero trade values and find that firms are less likely to trade with higher-tariff origins. Specifically, firms are less likely to continue importing higher-priced varieties from MFN origins in the context of higher most-favoured-nation tariffs. The findings emphasize the importance of varieties, defined as firm-origin combination, in import price analyses. We then move on to more aggregated analysis. After controlling for varieties, tariff pass-through to import prices is virtually complete (91 per cent). We find robust evidence that preference-partner countries take advantage of their tariff preference rent to increase prices. Lastly, we investigate the impact of other trade policy measures on importer prices. Restrictive trade measures such as anti-dumping, safeguards, and avian flu bans constrain imports effectively, through increasing prices of continuing varieties and the exit of varieties as they become prohibitively expensive. Liberalization events such as the US tariff rate quota have the opposite effect. These effects are large and more binding than most-favoured-nation tariffs-not surprising, as the other measures are more targeted and impose higher costs on specific foreign exporters and origins. Policy-makers should be cognisant of these dynamics when setting trade policy, particularly where structural impediments exist for local producers and when South African consumers' disposable income is increasingly constrained.
Keywords: F13; F14; F15; L11; 330; pass-through; preferential trade agreements; South Africa; imports; poultry